Delayed care seeking for fatal pneumonia in children aged under five years in Uganda: a case-series study - Karin Källander; Helena Hildenwall; Peter Waiswa; Edward Galiwango; Stefan Peterson; George Pariyo (Bulletin of the World Health Organization, 2008)
OBJECTIVE: To review individual case histories of children who had died of pneumonia in rural Uganda and to investigate why these children did not survive. METHODS: This case-series study was done in the Iganga/Mayuge demographic surveillance site, Uganda, where 67 000 people were visited once every 3 months for population-based data and vital events. Children aged 1-59 months from November 2005 to August 2007 were included. Verbal and social autopsies were done to determine likely cause of death and care-seeking actions. FINDINGS: Cause of death was assigned for 164 children, 27% with pneumonia. Of the pneumonia deaths, half occurred in hospital and one-third at home. Median duration of pneumonia illness was 7 days, and median time taken to seek care outside the home was 2 days. Most first received drugs at home: 52% antimalarials and 27% antibiotics. Most were taken for care outside the home, 36% of whom first went to public hospitals. One-third of those reaching the district hospital were referred to the regional hospital, and 19% reportedly improved after hospital treatment. The median treatment cost for a child with fatal pneumonia was US$ 5.8. CONCLUSION: There was mistreatment with antimalarials, delays in seeking care and likely low quality of care for children with fatal pneumonia. To improve access to and quality of care, the feasibility and effect on mortality of training community health workers and drug vendors in pneumonia and malaria management with prepacked drugs should be tested.